2015
DOI: 10.3762/bjnano.6.258
|View full text |Cite
|
Sign up to set email alerts
|

Large area scanning probe microscope in ultra-high vacuum demonstrated for electrostatic force measurements on high-voltage devices

Abstract: Summary Background: The resolution in electrostatic force microscopy (EFM), a descendant of atomic force microscopy (AFM), has reached nanometre dimensions, necessary to investigate integrated circuits in modern electronic devices. However, the characterization of conducting or semiconducting power devices with EFM methods requires an accurate and reliable technique from the nanometre up to the micrometre scale. For high force sensitivity it is indispensable to operate the microscope under high to ultra-high v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…It is found that Secondary Ion Mass Spectroscopy (SIMS) is difficult to be applied in case of power semiconductor devices because of the low dopant concentrations (as low as 10 14 cm -3 ) and narrow dimensions in the µm range. In this contribution, a dedicated Scanning Probe Microscope (SPM) [1], operated under ultra-high vacuum conditions, is applied for this purpose. An image of the scanning probe microscope instrument is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that Secondary Ion Mass Spectroscopy (SIMS) is difficult to be applied in case of power semiconductor devices because of the low dopant concentrations (as low as 10 14 cm -3 ) and narrow dimensions in the µm range. In this contribution, a dedicated Scanning Probe Microscope (SPM) [1], operated under ultra-high vacuum conditions, is applied for this purpose. An image of the scanning probe microscope instrument is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…(a) AFM with a 100x100 µm 2 closed loop scanner operating in UHV conditions with full optical access[1]. KPFM images of a silicon test structure (b) without and (c) with irradiation (about 20mW, =475-525nm) by sub-bandgap photons, respectively.…”
mentioning
confidence: 99%
“…All AFM measurements were performed by using a custom-built AFM operating under UHV and controlled gas pressures at RT. Our AFM is similar to the design in ref ( 23 ), however with a regular piezo-tube scanner instead of a closed-loop scanner. Commercially available Si cantilevers (Budget Sensors Tap150Al-G, k c ∼ 5 N m –1 ) were used as force sensors, which were annealed at 150 °C for 30 min in UHV prior to measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Since its invention, KPFM has been used to evaluate various electronic [3,[5][6][7][8][9][10][11][12][13] and ionic devices [14][15][16][17][18][19]. In particular, several reports have focused on the characterization of the built-in potential profiles in p-n junctions [5,8,9,11,12,[20][21][22], which are the key components of semiconductor devices. However, the magnitudes of the measured built-in potentials are smaller than those expected from the actual band structure.…”
Section: Introductionmentioning
confidence: 99%